Conditioned Actions in Strategic Coordination Games - Peter Engseld (Lund University, School of Economics and Management, Department of Economics, 2005)
A simple symmetric 2 "e 2 strategic coordination game is analyzed in an evolutionary environment under the assumption that agents are able to condition their actions on observations made of the opponent. Agents are assumed to be associated with a profile of characteristics, of which all agents can make a noisy observation. Actions can be conditioned on how the observed characteristics relates to that of their own. It is shown that there exist feasible states under which evolutionary pressure will transform any population conditioning its actions through a genetically induced continuous characteristic, such as body length, into a population conditioning its actions through Status, or how well agents have done in previous games. It is also shown that there does not exist feasible states by which a population conditioning its actions through Status could be invaded by any other strategies.
Keywords: C70; C72; 330; Coordination; Hawk-Dove Games; Status; Positional Concerns; Conditioned Strategies; Evolutionary Equilibrium